ANALISIS FAKTOR PADA MINAT MENABUNG NASABAH DI BANK MUAMALAT KABUPATEN BANYUWANGI DENGAN METODE CONFIRMATORY FACTOR ANALYSIS (CFA) - Ekaningsih, Lely Ana Ferawati; Budiywono, Eko; Wahyudi, Wahyudi (Relawan Jurnal Indonesia, 2024)
The aim of the research is to analyze the indicators in the Religiosity Factor (X1), Profit Sharing (X2), Location (X3), Product (X4), Trust (X5) and interest in saving iB Hijrah Haji savings customers (Y) at Bank Muamalat Sub-Branch Offices Whether the roof tile is still consistent with these variables or not after conducting research using the Confirmatory Factor Analysis (CFA) method. This type of research uses quantitative research with an ex-post facto approach. Results and conclusions of indicators that are consistent and have high factor loading values: religiosity factor (X1) with indicators of knowledge (intellectual), profit sharing factor (X2) with family indicators, location factor (X3) with indicators close to housing, product factors (X4 ) with product aesthetic indicators, trust factor (X5) with benevolence indicators, and interest (Y) with explorative indicators.